La scuola inclusiva come principio di equità: un traguardo per una educazione democratica - Guido Benvenuto (Firenze University Press, 2022)
National and international educational policies, with due differences, have always considered the issue of social and cultural inequalities with particular attention to re-organize the regulatory framework and improving the quality of teaching in educational contexts. In recent years, particular attention and, at the same time, concern have animated the public and political debate, introducing into the pedagogical lexicon dimensions concerning justice, equity and merit concerning academic results, performance, the achievement of skills, and, therefore, the need and methods of evaluation. Therefore, a fundamental antinomy has arisen in education policies: a school that wants to be inclusive must guarantee progress and educational success to each one, and therefore cannot be selective, that is, allow itself to leave someone behind and pursue merit, intended as a reward and waste recognition. A society and a school that want to enhance the differences and consider the specific needs of each one must reconsider the aims of education and instruction, in the perspective of educating society, guaranteeing everyone the achievement of transversal skills goals and professionalizing.